Projective Techniques and Psychological Assessment in Disadvantaged Communities. (June 2014) - Storey, Robert; Gapen, Mark; Sacco, James S.; Sacco, Frank C.
ABSTRACT This paper outlines the use of psychological testing in a community clinic. The emphasis is on the use of projective techniques in designing treatment plans for youth in disadvantaged communities. These assessments fall into three categories of testing referrals: determining mental impairment for disability, learning disability assessments, and diagnostic clarifications and treatment recommendations for therapists. The demands of psychological testing often require that the psychological evaluation play a role in how the client progresses in a system of care. Placement and risk decisions are often made in the psychological report. Projective techniques are stressed as a means to answer the most common questions asked from community referral agents such as schools, child protective case workers, courts, and human services agencies involved with residential programs. The relative strength of projective testing is compared with the value of empirical approaches stressed in modern psychology. Copyright © 2014 John Wiley & Sons, Ltd.